Molecular analysis of Candidate genes at the 22q region in Schizophrenia subjects - Bhoge Gowda, Kiran Kumar Halagur; Rao, Jay; O'Reilly, Richard; Singh, Shiva M. (Research in Biotechnology, 2012)
22q11.2 deletion syndrome (22q11.2DS), also known as Velo-Cardio-Facial Syndrome (VCFS) or DiGeorge Syndrome, is a genetic disorder due to a micro deletion on chromosome 22q11.2. VCFS is associated with abnormalities in brain structure and with an increased risk of psychiatric disorders, particularly schizophrenia (SCZ). DNA copy number is a largely unexplored source of human genetic variation that may contribute risk for complex disease like SCZ. The aim of this study was to assess Copy number variations (CNV) at candidate genes located in 22q11 region in SCZ subjects. We report aberrations in copy number at PRODH and COMT gene loci supporting the hypothesis that dosage effects of 22q genes could lead to disruptions in neurotransmitter signaling and related neurobehavioral symptoms observed in SCZ subjects. The results support the hypothesis that the complex phenotype of 22qDS results either from the overlapping regulation of several genes within this region or from its concerted participation in a highly regulated process.